KLLN epigenotype–phenotype associations in Cowden syndrome - Nizialek, Emily A (Eur J Hum Genet, 2015)
Germline KLLN promoter hypermethylation was recently identified as a potential genetic etiology of the cancer predisposition syndrome, Cowden syndrome (CS), when no causal PTEN gene mutation was found. We screened for KLLN promoter methylation in a large prospective series of CS patients and determined the risk of benign and malignant CS features in patients with increased methylation both with and without a PTEN mutation/variant of unknown significance. In all, 1012 CS patients meeting relaxed International Cowden Consortium criteria including 261 PTEN mutation-positive CS patients, 187 PTEN variant-positive CS patients and 564 PTEN mutation-negative CS patients, as well as 111 population controls were assessed for germline KLLN promoter methylation by MassARRAY EpiTYPER analysis. KLLN promoter methylation was analyzed both as a continuous and a dichotomous variable in the calculation of phenotypic risks by stepwise logistic regression and Kaplan–Meier/standardized incidence ratio methods, respectively. Significantly increased KLLN promoter methylation was seen in CS individuals with and without a PTEN mutation/VUS compared with controls (P<0.001). Patients with high KLLN promoter methylation have increased risks of all CS-associated malignancies compared with the general population. Interestingly, KLLN-associated risk of thyroid cancer appears to be gender and PTEN status dependent. KLLN promoter methylation associated with different benign phenotypes dependent on PTEN status. Furthermore, increasing KLLN promoter methylation is associated with a greater phenotype burden in mutation-negative CS patients. Germline promoter hypermethylation of KLLN is associated with particular malignant and benign CS features, which is dependent on the PTEN mutation status.